SMARCA4-deficient Undifferentiated Uterine Sarcoma: Clinicopathological Features of an Emerging Entity. (February 2023) - Nakra, Tripti; Kakkar, Aanchal; Mathur, Sandeep R.; Jain, Deepali; Kumar, Sunesh
SMARCA4 -deficient undifferentiated uterine sarcoma is a recently described molecularly defined entity among the subset of aggressive undifferentiated uterine tumors. Mutation in the SMARCA4 gene is a key driver alteration, as also seen in small cell carcinoma of ovary, hypercalcemic type (SCCOHT) and thoracic undifferentiated carcinoma. Limited number of cases of SMARCA4-deficient undifferentiated uterine sarcoma has been reported in literature. We hereby describe a case of this distinct entity in a 52-year-old woman. Histomorphological examination showed sheets of monomorphic epithelioid cells with a variable proportion of cells displaying rhabdoid features, brisk mitotic activity, and lymphovascular invasion. A panel of immunohistochemical markers was required to exclude the differential diagnoses. The tumor was microsatellite stable. Loss of SMARCA4 expression and intact expression of INI1 in tumor cells by immunohistochemistry (IHC) confirmed the diagnosis of SMARCA4- deficient undifferentiated uterine sarcoma. The patient had a rapidly progressive clinical course.